Las Tecnologías de información y comunicación (TICs) como respuesta a necesidades educativas del medio rural - Víquez Salazar, Marlene (2008)
The article must like intention reflect, from a critical perspective, on the use of the technologies of the information and the communications (TIC) in the rural education, under the assumption that these resources are not in themselves solutions to problems, but that can allow to obtain solutions to concrete problems, in the scope of the rural education. For it, an analysis becomes from different edges.